Implementasi Hasil Perancangan Sistem Pelacakan dengan Menggunakan Antena Tracking Sistem - Meitri Kristiani Simamora (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
Orbital perturbation is a phenomenon in which the orbit of a satellite changes due to one or more external influences such as an anomaly in the Earth's gravitational distribution, gravitational disturbances from the moon, meteor impacts or other objects, or solar radiation pressure. These maneuvers use small rockets (thrusters) that are on the satellite body and the direction is set according to the correction direction. Ignition of these small rockets will consume fuel brought by satellites from Earth as a provision. Communications satellites have demonstrated their capabilities since the last three decades. that the communication satellite mission in the 60s was an alternative point-to-point transmission between continents, due to its ability to see approximately one third of the earth's surface from the geostationary orbit altitude just above the equator.